Participatory Management and Local Culture : Proverbs and Paradigms - Easton, Peter (World Bank, Washington, DC, 2012)
Whereas evaluation has often been considered an activity required by donors, but fundamentally foreign to local culture, there is however plenty which has been done recently to develop participatory, and empowering modes of program evaluation, giving local stakeholders active roles, and a say in how evaluation is performed. Furthermore, unanticipated results of participatory evaluation practices in West Africa has brought to light local attitudinal approaches to evaluation, thus creating a basis for the development of an appropriate evaluation methodology. Incredibly, one of the means for such results was the use of proverbs, which encapsulate local attitudes, and provide insight in evaluation-related issues, such as accountability, performance, and social responsibility. Such "proverbial" culture placed evaluation at its best form of collective decision-making, making the participatory approach to evaluation a leitmotif. This attitude creates the basis for helping beneficiaries develop a culturally-appropriate technology of democratic self-governance.